2009
DOI: 10.1093/nar/gkp012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of translation termination mechanism identifies two new critical regions in eRF1

Abstract: Translation termination in eukaryotes is completed by two interacting factors eRF1 and eRF3. In Saccharomyces cerevisiae, these proteins are encoded by the genes SUP45 and SUP35, respectively. The eRF1 protein interacts directly with the stop codon at the ribosomal A-site, whereas eRF3—a GTPase protein—probably acts as a proofreading factor, coupling stop codon recognition to polypeptide chain release. We performed random PCR mutagenesis of SUP45 and screened the library for mutations resulting in increased eR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…The type and position of amino acid substitution can also affect the phenotype. The best studied model systems, such as E. coli and S. cerevisiae , have revealed complex determinants extending at least six base pairs downstream of the stop codon itself [ e.g., (Poole et al 1998; Namy et al 2001; Poole et al 2003; Hatin et al 2009)]. Our findings are consistent with such mechanisms operating in S. pombe , too.…”
Section: Discussionsupporting
confidence: 88%
“…The type and position of amino acid substitution can also affect the phenotype. The best studied model systems, such as E. coli and S. cerevisiae , have revealed complex determinants extending at least six base pairs downstream of the stop codon itself [ e.g., (Poole et al 1998; Namy et al 2001; Poole et al 2003; Hatin et al 2009)]. Our findings are consistent with such mechanisms operating in S. pombe , too.…”
Section: Discussionsupporting
confidence: 88%
“…This study extended the cavity model by suggesting that conformational changes hinging around the TASNIKS motif optimize the relative orientation of the cavities for decoding of UAA/UAG on one hand and UGA on the other. Lastly, based on the results of an anti-suppressor screen, Hatin et al (6) identified two new regions important for stop codon decoding they termed pocket one and two (Figure 7), which were proposed to be involved in maintaining an overall structural frame-work of the N-domain that is optimal for eRF1 function in translation termination.
Figure 7.Stop codon specificity of read-through in eRF1 N-domain mutants.
…”
Section: Discussionmentioning
confidence: 99%
“…The shape of human eRF1 resembles a tRNA, with functional motifs targeting both the peptidyl transferase center and the decoding site. eRF1 recognizes all three stop codons through an extended area in its N-terminal domain [21][22][23], although it has recently become clear that eRF1 acts differently depending on the type of codon; its behavior with UGA being different from that with UAA or UAG [21,24]. When a stop codon is recognized, the highly conserved Gly-Gly-Gln (GGQ) motif in the central domain of eRF1 triggers peptidyl-tRNA hydrolysis by activating the peptidyl transferase center of the ribosome [25][26][27].…”
Section: Mechanisms Of Translation Terminationmentioning
confidence: 99%